2007
DOI: 10.1108/00251740710745025
|View full text |Cite
|
Sign up to set email alerts
|

Corporate strategy and shareholder value during decline and turnaround

Abstract: PurposeThe paper aims to assess the impact of corporate strategy on shareholder value in decline and turnaround situations.Design/methodology/approachA sample of 45 turnaround firms was selected and matched against a control sample which did not face continuous decline over the time period studied. The impact of corporate strategy on shareholder value was tested using cumulative beta excess return measures to capture the long‐term basis of corporate strategy.FindingsThe paper finds that the beta excess return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 93 publications
1
12
0
1
Order By: Relevance
“…Regarding managerial cognition, we illustrated the importance of managerial cognition in shaping turnaround strategising practices, in that, we have confirmed that management's awareness of decline and their perception of the declines severity, were found to have a profound effect on the timing and intensity of actions taken (also found by Furrer et al 2007). Given the critical role that stakeholders play in the turnaround process, two key dimensions emerged from the data; stakeholder influences, and stakeholder relationships.…”
Section: Response Factorssupporting
confidence: 59%
“…Regarding managerial cognition, we illustrated the importance of managerial cognition in shaping turnaround strategising practices, in that, we have confirmed that management's awareness of decline and their perception of the declines severity, were found to have a profound effect on the timing and intensity of actions taken (also found by Furrer et al 2007). Given the critical role that stakeholders play in the turnaround process, two key dimensions emerged from the data; stakeholder influences, and stakeholder relationships.…”
Section: Response Factorssupporting
confidence: 59%
“…However, empirical results remain inconclusive; Andrade and Kaplan (1998) state that CAPEX reductions are inevitable for firms in distress, and Sudarsanam and Lai (2001) cannot find any significant influence. Moreover, Furrer et al (2007) postulate that CAPEX negatively relates to market performance in the years immediately after a turnaround, and only reveals positive effects in subsequent mid-term years. Hence, significant performance enhancement can be expected only if accompanied by strategic asset retrenchment or portfolio restructuring (Lins et al 2013;Pearce and Robbins 1993).…”
Section: Capital Expendituresmentioning
confidence: 99%
“…However, Hotchkiss (1995) offers contradictive results that employ accounting measures, predominantly used in general management research. Although scholars rely on market measures to argue that relative and absolute accounting measures can be subject to managerial manipulation, the counterparty claims market measures are biased by expectations (Eberhart et al 1999;Franzen et al 2007;Furrer et al 2007).…”
Section: Turnaround Outcomementioning
confidence: 99%
“…Regarding the decline literature, one inference we can draw is that those private sector studies emphasizing market and financing strategies typically have limited relevance for public administration. Likewise, studies focusing on shareholders (Furrer, Pandian, and Thomas 2007), asset costs and depreciation (Morrow, Johnson, and Busenitz 2004), and stock and corporate boards (Mueller and Barker 1997) seem to have limited relevance. Even studies focusing on technological innovation seem to have limited relevance.…”
Section: The Irrelevance Of the Generic Decline Literaturementioning
confidence: 99%